2016
DOI: 10.1016/j.jbiosc.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of partitioning behaviors of immunoglobulin G in polymer-salt aqueous two-phase systems

Abstract: The partitioning behavior of immunoglobulin G (IgG) in the aqueous two-phase system (ATPS) composed of poly(ethylene glycol) (PEG) and phosphate was studied. The parameters of ATPS exhibiting the pronounced effects on the partitioning behavior of IgG include phase composition, PEG molecular weight, and the addition of sodium chloride (NaCl). The accumulation of IgG at the interface of the ATPS increased drastically as the tie-line length (TLL) was increased. This trend was correlated with a linear relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…proposed the use of ABS for the purification of IgG from human plasma. Studies on the partitioning of pure IgG, obtained from human serum, have also been reported, as well as on the purification of IgG from transgenic plants …”
Section: Introductionmentioning
confidence: 99%
“…proposed the use of ABS for the purification of IgG from human plasma. Studies on the partitioning of pure IgG, obtained from human serum, have also been reported, as well as on the purification of IgG from transgenic plants …”
Section: Introductionmentioning
confidence: 99%
“…ATPS can be formed by dissolution of polymer/polymer, polymer/salt, ionic liquid/salt, alcohol/salt or cationic/anionic surfactants in water at certain equilibrium concentrations and conditions, such as pH, temperature and pressure . This liquid–liquid extraction process has the advantages of non‐toxicity, short‐phase separation time, purification ease, high selectivity, low cost and few equipment requirements .…”
Section: Introductionmentioning
confidence: 99%